Developing Religious Character in Early Childhood: Daily Habituation Model in Islamic Kindergartens - Nafsaka Sajidin, Zayin (Sekolah Tinggi Agama Islam Kuningan, 2025)
Backround: This study investigates the implementation and effectiveness of daily habituation models in developing religious character among early childhood students in Islamic kindergartens.Objective: The research addresses the gap between theoretical frameworks of Islamic character education and practical implementation strategies in early childhood settings.Method: Using a mixed-methods approach, data were collected from 156 children aged 5-6 years across six Islamic kindergartens in Indonesia through observation protocols, teacher interviews, parent questionnaires, and character assessment instruments.Findings and Implications: Quantitative analysis employed paired sample t-tests and ANOVA, while qualitative data were analyzed thematically. Results revealed that systematic daily habituation significantly improved children's religious character indicators (p < 0.001), with effect sizes ranging from medium to large (Cohen's d = 0.68-1.24). Five core habituation patterns emerged: ritual worship practices, moral behavioral routines, Islamic social etiquette, Quranic literacy activities, and prophetic character modeling.Conclusion: The study demonstrates that structured, consistent, and contextually integrated daily routines serve as effective pedagogical tools for character formation in early childhood. Implications suggest that Islamic kindergartens should prioritize authentic, experiential learning environments over didactic instruction, emphasizing teacher modeling, peer interaction, and family-school partnership in character development programs.